Substitusi Tepung Ikan Dengan Maggot (Hermetia illucens) Terhadap Efisiensi Dan Pertumbuhan Ikan Mas (Cyprinus carpio L) - Jens Tindage; Jeffrie F. Mokolensang; Revol D. Monijung; Cyska Lumenta; Joppy D. Mudeng; Edwin L. A. Ngangi (e-Journal BUDIDAYA PERAIRAN, 2023)
Fish farming is raising fish rationally including controlling growth and breeding which allows supervision, especially in terms of regulating reproduction and feeding. One of the ways to increase aquaculture production is by conducting research to produce economical feed with nutritional content according to the needs of fish. Fishmeal is generally used as a source of animal protein in feed, but its availability is still fluctuating due to the high price of fishmeal, therefore an alternative feed is urgently needed. Alternative source of protein is maggot, black soldier fly larvae can be used as a good source of nutrition because they contain protein, lipids and minerals. The purpose of this study was to examine the growth of carp fed with the addition of maggot 40 g, 30 g, 20 g 10 g, and pellets without maggot had significant effect on growth, feed efficiency and feed convercion ratio. This study used an experimental design based on a completely randomized design (CRD) with 5 treatments each with three replications. Statistically showed that substitution of fish meal with maggot had significant effect on growth, feed efficiency and feed convercion ratio. Â The addition of 30 g maggot into feed (treatment B) gave better results compared to other treatments. Fish fed treatment B had survival rate of 80%, absolute growth of 3.63 g, relative growth 137.9% and daily 2.8%.Â  Feed efficiency and feed conversion ratio in treatment B were 66.44% and 1.51, respectively. Keywords: aquaculture, fish feed, alternative protein source, food conversion ratio